"Overcoming anxiety, panic and depression" - "Gardner, James" (New Delhi, 2003)
Explores the chemical and non-chemical approaches to common forms of anxiety, panic disorders, and depression, explaining the difference between specific and social phobias and panic and generalized anxiety disorder.
Keywords: Depression